Pressing issues for oral health care access and quality improvement during pregnancy in Portugal - a qualitative study - Frey Furtado, Leonor; Melo, Paulo; Listl, Stefan; Pereira, Maria Lurdes (Journal of public health dentistry, 2025)
Objective To identify and prioritize pressing issues related to access and quality of oral healthcare during preconception, pregnancy, and postpartum in Portugal. Methods Ethical approval (number 8/2024) and data protection clearance (R-12/2024) were granted. Twelve stakeholders, including healthcare professionals, policymakers, representatives of nongovernmental organizations, and recent mothers, were recruited through snowball sampling. The Nominal Group Technique structured a four-step process: (1) online discussions at policy, community, and practice levels; (2) initial voting to screen pressing issues; (3) plenary discussion; and (4) final voting. Results At the policy level, the highest-ranked pressing issues were the lack of a mandatory oral health diagnostic appointment for early detection, limited coverage of the Cheque-Dentista program, which excludes the preconception period, and the absence of oral health education in childbirth and parenting courses. At the community level, pressing issues included the absence of oral health in family planning consultations, insufficient oral health training for midwives and nurses, and weak direct engagement with pregnant women through targeted promotion strategies. At the practice level, the most pressing issues were the exclusion of dentists from maternal healthcare teams, the lack of structured oral health appointments in primary healthcare centers, and the omission of oral health modules from childbirth preparation programs. Conclusion The Nominal Group Technique enabled consensus-building and prioritization of concrete pressing issues, producing actionable strategies to strengthen maternal oral healthcare in Portugal. Literacy, accessibility, and collaboration have emerged as foundational elements for integrating oral health into maternal care pathways.